IMPROVING EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE AND WORK MOTIVATION - Asmawiyah Asmawiyah; Nurlinda Nurlinda; Nurwana Nurwana (Universitas Indo Global Mandiri Palembang, 2026)
Objective: This study aims to empirically examine and test the influence of work discipline and work motivation on employee performance. This research is expected to make theoretical and practical contributions to the development of human resource management strategies, particularly to improve productivity and the quality of organizational performance. Design/Methods/Approach: This study used a quantitative, associative approach. The study population comprised all employees of the M Regency Makassar Hotel, with a sample of 46 respondents selected using a saturated sampling technique. Data were collected via a Likert-scale questionnaire and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with SmartPLS software. This included validity, reliability, coefficient of determination, and hypothesis testing. Findings: The results indicate that work discipline and work motivation have a positive and significant effect on employee performance. Work discipline has a more dominant influence than work motivation. These findings suggest that compliance with work rules and employee internal motivation are important factors in improving performance. Originality/Value: This research makes an empirical contribution to the study of human resource management, particularly in the hospitality sector, which remains relatively under-researched. Furthermore, the use of the SEM-PLS method provides a more comprehensive analytical approach for examining relationships among variables. Practical/Policy Implications: The results of this study imply that hotel management should improve work discipline by implementing strict rules and increasing employee motivation through rewards, career development, and a supportive work environment to achieve optimal employee performance.